ANALISIS SPASIAL KEJADIAN TUBERKULOSIS DENGAN ASPEK KESEHATAN LINGKUNGAN DI WILAYAH KERJA PUSKESMAS KUNDURAN KABUPATEN BLORA TAHUN 2021 - maharrani, agustia hera; wulandari, fitria; wardoyo, Agung (Universitas PGRI Semarang, 2025)
Abstrac One of the infectious diseases that causes tuberculosis is Mycobacterium tuberculosis, which is still a health problem in Indonesia. The number of Tuberculosis cases in Kunduran District is 28 cases in 2021. The purpose of this study is to spatially analyze the distribution of Tuberculosis cases in the Kunduran Health Center Work Area based on age, gender, education, occupation, smoking habits, alcohol consumption habits, environmental conditions of patients which includes house ventilation, house floor type, house wall type, temperature, house occupancy density, and humidity.Observational research with the interview method is the type of research used in this study. The population in this study were all tuberculosis patients. Tuberculosis patients with complete addresses were used as research samples. Data on pulmonary tuberculosis patients were obtained from the UPTD of the Kunduran Health Center. Respondent identity data obtained from interviews and the location of the coordinates through the Google Maps application. Data analysis was performed using the Statistical Package for the Social Sciences (SPSS) and Quantum GIS software.The results of the study revealed that the majority of respondents were of productive age (15-64 years) (82.6%), male (60.9%), elementary school education level (56.5%), working (60.9% ), has no history of alcohol consumption (100%), smoking (52.2%), house ventilation that meets the requirements (60.9%), floor of the house that does not meet the requirements (56.5%), walls of the house that do not meet the requirements requirements (52.2%), house temperature that does not meet the requirements (69.6%), occupancy density of houses that meet the requirements (82.6%), humidity that meets the requirements (95.7%). Suggestion: The health office and Puskesmas can provide education on healthy homes and clean and healthy living behaviors